PENAMBAHAN TEPUNG TEMPE, TEPUNG UDANG REBON DAN PERISA DALAM PEMBUATAN KUKIS SUKUN - Hermansyah Silitonga; Netti Herawati; Vonny Setiaries Johan (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purpose of this study were to obtain the best composition the addition of tempeh flour and rebon shrimp flour for making breadfruit cookies and meet the quality standards of cookies (SNI 01-2973-1992) and to determine the level of the children's favorite for the best breadfruit cookies with the addition of various flavor. This research used a completely randomized design (CRD) with 4 treatments and 4 replications. The treatments in this study were S1 (Tempeh flour 20%, small shrimp flour 1%), S2 (Tempeh flour 15%, small shrimp flour 6%), S3 (Tempeh flour 10%, small shrimp flour 11%) and S4 (Tempeh flour 5%, small shrimp flour 16%). The data obtained were analyzed statistically using Anova and further tested with DNMRT at the level of 5%. The treatments gave significant effect on moisture, protein, ash and fat content. The best treatment on this research was breadfruit cookies with addition of tempeh flour 20% and small shrimp flour 1%, with moisture content of 6.75%, protein content of 13.87%, ash content of 1.87% and 35.56% fat content. The addition of various flavor on S1 cookies gave non significant affect on the childrens organoleptic test. Keywords : Cookies, breadfruit, tempeh flour, small shrimp flour, flavor